Residents’ perceptions towards tourism activity: the case of Bragança, Portugal - Rodrigues, Cláudia Alexandra da Silva (2024)
Residents’ perceptions of tourism can vary depending on the location, context, and individual experiences. Tourism is commonly perceived as a potential economic resource, presenting features that can increase quality of life. However, there are concerns about the negative effects of tourism on the quality of life of residents living in these destinations. In this sense, this study aims to understand the residents’ perceptions of the effects of tourism in Bragança, Portugal, and whether there are any variations in how residents perceive the activity, particularly if the residents’ involvement withtourism leads to any changes in these perceptions. The research was conducted by collecting data through 203 online questionnaires,analysing the data obtained using both descriptive and inferential analysis. This study reveals residents’ overall positive perceptions and recognition of tourism’s economic potential, including job creation and revenue generation. However, concerns were raised about tourism’s adverse effects on quality of life, such as pollution and traffic congestion. The research emphasises the need for resident-inclusive tourism planning and enhanced communication to ensure mutually beneficial outcomes for tourists and the local community.